Penerapan Metode Big M dalam Pengoptimalan Hasil Produksi dan Analisis Sensitivitas (Studi Kasus: UMKM Rempeyek Ilham Jambi) - Ningsih, Wahyu; Rozi, Syamsyida; Multahadah, Cut (Square : Journal of Mathematics and Mathematics Education, 2024)
In industrial businesses, a strategy for optimizing production results is an important thing to consider carefully so that the production process runs as efficiently as possible and the results obtained are feasible and optimal. This also needs to be a consideration for UMKM Rempeyek Ilham which are engaged in the production of peanut brittle. So, the aim of this research is to identify the number of optimal productions at UMKM Rempeyek Ilham so that maximum sales results can be obtained through modeling in the form of a linear program. However, the constraints formed in the linear programming model have sign of ≥, which cannot be resolved using the simplex method. One method that can be used to find a feasible and optimal solution for a linear programming model that has constraints ≥ is the Big M method. Therefore, in this research the Big M method is applied to find a feasible and optimal solution to the linear programming model. This research produces information about the number of optimal productions of peanut brittle with maximum sales of IDR 6,800,000.00. Furthermore, in this research a sensitivity analysis was also carried out to anticipate several possible changes that would occur so that the optimal solution obtained did not change or could even increase.Keywords: Big M method, Linear programming, Optimization, Sensitivity analysis.